Entropy-Based Pandemics Forecasting - Lucia, Umberto; Deisboeck, Thomas S.; Grisolia, Giulia (Frontiers in Physics, 2020)
A great variety of natural phenomena follows some statistical distributions. In epidemiology, such as for the current COVID 19 outbreak, it is essential to develop reliable predictions of the evolution of the epidemics or pandemics. In particular, a statistical projection of the time of maximum diffusion of infected carriers is fundamental in order to prepare healthcare systems and organise a robust public health response. In this paper, we develop a thermodynamic approach based on the infection statistics related to the total citizenry of a country. It represents a novel tool for evaluating the time of maximum diffusion of the infection.